THE COMMUNITY EMPOWERMENT IN TRAINING IN THE PRODUCTION OF SACHA INCHI OIL AS AN ECONOMIC ALTERNATIVE IN JAMBANGAN, SURABAYA - Surjaningsih, Dwi Retno; Joeniarti, Elika; Susilo, Achmadi; Thohiron, M.; Nisak, Salsabila Safirotun; Pambudi, Satrio Wahyu Agung (International Journal of Engagement and Empowerment (IJE2), 2023)
This community service activity aims to empower the community in Jambangan Village, Surabaya, through training in making Sacha Inchi Oil as an economic alternative. With support from PT. Pertamina Integrated, this program emphasizes increasing skills and knowledge in the process of processing Sacha Inchi into oil with high economic value. This training is designed to increase community understanding of local potential that can be processed sustainably, while creating alternative sustainable livelihoods. Through structured training sessions, participants will be introduced to modern techniques in processing Sacha Inchi, including production and quality control steps. The importance of economic sustainability and food security in sub-districts is the main focus of this activity. Participants will be equipped with practical knowledge and technical skills to start and manage Sacha Inchi Oil production independently. Apart from that, PT. Pertamina Integrated also provides assistance in the form of facilities and equipment needed to increase the community's production capacity. It is hoped that the results of this activity will have a positive economic impact in Jambangan Village, as well as strengthening the independence and economic resilience of the local community. Apart from that, it is hoped that this training will be able to create a model of community empowerment that can be adopted in surrounding areas, creating positive change in a wider scope